The Influence of Parental Parenting on the Character Formation of Elementary School Students - Kafara, Ibnu Ahmad Rifa'i; Harlanu, Muhammad; Sumartiningsih, Sri; Yuwono, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
This research departs from the fact that there are still few studies that discuss how parenting at home affects the character development of children in elementary school. In fact, parenting at home plays a big role in shaping children's values, attitudes, and behaviors, both at school and in daily life. This study aims to explain the influence of parental parenting on the character development of elementary school students through literature studies. The method used is qualitative descriptive with data collected from various academic journals through platforms such as Google Scholar and Publish or Perish. The results of the analysis show that parental parenting has a significant effect on the formation of children's character, both in the school environment and in daily life. These findings confirm the importance of collaboration between schools and parents in designing parenting styles that support children's character development. In addition to enriching theoretical studies on family-based character education, this study also provides practical recommendations for the development of more effective parenting.